2008
DOI: 10.1097/moh.0b013e328309ec74
|View full text |Cite
|
Sign up to set email alerts
|

The platelet release reaction: just when you thought platelet secretion was simple

Abstract: Purpose of the Review-In response to agonists produced at vascular lesions, platelets release a host of components from their three granules: dense core, alpha, and lysosome. This releasate activates other platelets, promotes wound repair, and initiates inflammatory responses. While widely accepted, the specific mechanisms underlying platelet secretion are only now coming to light. This review focuses on the core machinery required for platelet secretion.Recent Findings-Proteomic analyses have provided a catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
74
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 48 publications
4
74
0
1
Order By: Relevance
“…[1][2][3] Dense granules harbor small molecules that upon release amplify platelet activation and adhesion, blood vessel constriction, and wound repair. [4][5][6] a granules store protein factors that facilitate platelet adhesion, clot stabilization, fibrinolysis, angiogenesis, wound repair, and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Dense granules harbor small molecules that upon release amplify platelet activation and adhesion, blood vessel constriction, and wound repair. [4][5][6] a granules store protein factors that facilitate platelet adhesion, clot stabilization, fibrinolysis, angiogenesis, wound repair, and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Dense granules contain small molecules, notably adenosine diphosphate (ADP) and adenosine triphosphate (ATP), as well as histamine and serotonin. 21 Upon platelet activation with strong agonists, these granules are first centralized and then secreted, 22,23 which is essential for the recruitment of further platelets, thereby promoting platelet aggregation and thrombus growth.Despite a number of previous studies on the function of Cdc42 in platelets, its role in platelet activation and cytoskeletal reorganization, as well as its impact on degranulation and thrombus formation, is currently unclear. The online version of this article contains a data supplement.…”
mentioning
confidence: 99%
“…Platelets contain vesicle-membrane SNAREs (vSNAREs), including VAMP-2, -3, -7, and -8, and target-membrane SNAREs (t-SNAREs), including syntaxin 2, 4, 7, and 11, and SNAP-23, -25 and -29. 4 Studies have shown that syntaxin 2 and SNAP-23 are involved in all 3 platelet granule secretion events, whereas syntaxin 4 mediates ␣-granule and lysosome release. VAMP-8 is the primary v-SNARE required for secretion of all platelet granules.…”
mentioning
confidence: 99%
“…2 The molecular mechanisms involved in platelet granule secretion are complex and incompletely understood. [3][4][5] Platelet activation involves several rapid events, including shape change, aggregation, and granule secretion, and it is difficult to discern the cellular mechanisms involved. Electron microscopy studies have revealed that platelet shape changes are accompanied by cytoskeletal rearrangements and centralization of granules.…”
mentioning
confidence: 99%